1999
DOI: 10.1046/j.1365-2648.1999.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Levels’ of attainment in nursing practice: reality or illusion?

Abstract: In earlier research based on an analysis of course documentation, it had been found that there was little consensus among nurse educators concerning the parameters which distinguish levels of practice skills, particularly those which differentiate diploma and degree qualifications in the United Kingdom. This result was confirmed and strengthened in the current study. Lecturers in nursing, when presented with a sorting task using 40 statements derived from course documentation selected from the earlier study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…However, although in some countries such as Australia, clear distinctions between the two qualification are distinguished, (Australian Qualification Framework, 2013), Warring (2011) failed to find any difference in learning levels in the specific qualifications in a New Zealand polytechnic. Similar findings were observed in the case of nursing's practices for degree and diploma qualifications in the United Kingdom (Ashworth, Gerrish, Hargreaves & McManus, 1999). In South Africa the Department of Higher Education and Training distinguishes between diplomas and degrees in the characteristic of graduates and levels and types of competencies (Republic of South Africa, 2013).…”
Section: Theoretical Framework: Diplomas or Degrees In Universities Osupporting
confidence: 61%
“…However, although in some countries such as Australia, clear distinctions between the two qualification are distinguished, (Australian Qualification Framework, 2013), Warring (2011) failed to find any difference in learning levels in the specific qualifications in a New Zealand polytechnic. Similar findings were observed in the case of nursing's practices for degree and diploma qualifications in the United Kingdom (Ashworth, Gerrish, Hargreaves & McManus, 1999). In South Africa the Department of Higher Education and Training distinguishes between diplomas and degrees in the characteristic of graduates and levels and types of competencies (Republic of South Africa, 2013).…”
Section: Theoretical Framework: Diplomas or Degrees In Universities Osupporting
confidence: 61%
“…For example, Girot (2000)– who has addressed the issues of reliability and validity in clinical competence assessment (1993) – points out that we are unable to articulate different levels of competence, for example between diplomate and graduate. If this is the case, then it is hard to imagine how purported levels could be measured and this is supported by Ashworth et al . (1999) who demonstrated that lecturers were, indeed, unable to distinguish between supposed diploma and degree competencies when presented out of context.…”
Section: Assessment Of Competencementioning
confidence: 99%
“…For example, Girot (2000) -who has addressed the issues of reliability and validity in clinical competence assessment (1993) -points out that we are unable to articulate different levels of competence, for example between diplomate and graduate. If this is the case, then it is hard to imagine how purported levels could be measured and this is supported by Ashworth et al (1999) who demonstrated that lecturers were, indeed, unable to distinguish between supposed diploma and degree competencies when presented out of context. Research has already been referred to (Norman et al 2000), which demonstrated the lack of reliability and validity in current assessment instruments for clinical competence assessment and this was underpinned by the work of Coates and Chambers (1992), who earlier demonstrated the lack of any systematic approach to the development of clinical competence assessment instruments.…”
Section: Assessment Of Competencementioning
confidence: 99%
“…Research (Gerrish et al . 1997, Ashworth et al . 1999) has highlighted the difficulties nurse educators experienced in differentiating between academic levels and a lack of shared understanding regarding performance in practice at diploma, degree and master's level.…”
Section: Introductionmentioning
confidence: 99%